2017
DOI: 10.12657/denbio.079.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the height stability in progeny of Fagus sylvatica L. populations using the GGE biplot method

Abstract: Forecasted climate changes demand selection of populations (seed stands) and genotypes (plus trees) best adapted to changing environmental conditions and displaying limited genotype × environment (G×E) interaction. Analysis of multi-environment trials (METs) allows to recognize differences between populations and environments, as well as G×E interaction. To define stability of tree height we used a GGE biplot graphic method based on the results of measurement of 5-and 10-year-old trees originating from 30 Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…International beech provenance trials have shown that not all provenances interact with local climate (Ivankovic et al 2008;Jastrzebowski et al 2017), but the decrease in height growth was not significant when provenances were moved to a cooler and wetter environment (Mátyás et al 2009). However, the effect of ecodistance, which refers to environmental change that each provenance experienced because of translocation to the provenance trial site (Mátyás et al 2009), was visible in height growth at the Slovenian site (Železnik et al 2019).…”
Section: Application Of the Results In Practicementioning
confidence: 99%
“…International beech provenance trials have shown that not all provenances interact with local climate (Ivankovic et al 2008;Jastrzebowski et al 2017), but the decrease in height growth was not significant when provenances were moved to a cooler and wetter environment (Mátyás et al 2009). However, the effect of ecodistance, which refers to environmental change that each provenance experienced because of translocation to the provenance trial site (Mátyás et al 2009), was visible in height growth at the Slovenian site (Železnik et al 2019).…”
Section: Application Of the Results In Practicementioning
confidence: 99%
“…In recent years, analysis of variance in multi-environment trials (MET) has been performed according to the mixed model framework [41][42][43][44]. Depending on the needs, the effects of genotypes (in this study populations) and environments (in this study experimental sites) are treated as fixed or random [43][44][45][46]. In order to investigate the environmental impact and the differentiation of genotypes in terms of height, a linear mixed model was considered:…”
Section: Bioclimatic Variablesmentioning
confidence: 99%
“…However, the northeastern border of its natural range is limited by both cold temperatures and drought ( Bolte et al., 2007 ; Kreyling et al., 2014 ; Matisons et al., 2017 ; Farahat and Linderholm, 2018 ). There is a growing concern about the future survival and sustainability of beech ecosystems throughout Europe ( Geßler et al., 2007 ; Aranda et al., 2015 ; Jastrzębowski et al., 2017 ), as beech may be unable to adapt to future environmental conditions in its current natural range ( Lakatos and Molnár, 2009 ; Bellard et al., 2012 ; Stojnić et al., 2018 ). Protection of genetic diversity is essential both for economic reasons and to guarantee the adaptability of the common beech towards climatic changes ( Bohn et al., 2000 ; Staszak and Pawłowski, 2012 ; Staszak et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%